Negative Social Interaction and Psychological Well-Being on Female Basketball Athletes - Umniyah, Zulfa Nur; Berliana, Berliana; Mulyana, Boyke; Novian, Geraldi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2021)
Exercise can maintain a person's level of psychological well-being or also known as Psychological well-being (PWB), but on the other hand, it can also have a negative effect. Negative Social Interaction is one of the factors that have a negative effect on individuals from their environment during exercise. In terms of gender, women and sports are interrelated even though women have long been underestimated in sports, especially in sports that are considered masculine sports. This study examines the negative social interactions experienced by athletes in basketball. In basketball, negative social interactions can occur due to the assumption that basketball is a masculine sport, besides, that women are considered weaker than men. So this study aims to analyze the impact of Negative Social Interaction obtained by female basketball athletes on the Psychological well-being (PWB) of athletes. The instruments used were Negative Social Exchange (NSE) and Psychological Well-being Scale questionnaires as well as short interviews given to 24 female basketball athletes at the University of Indonesia Education. The results showed that NSI had a significant relationship with the PWB of female basketball athletes. The coach is one individual who plays a very important role in the condition of the athlete's PWB. Not only can it have a negative impact, but NSI can also be turned into a motivation that can encourage athletes to fight harder in the future. The author provides suggestions for coaches who handle female basketball athletes to be more careful when interacting with athletes and for basketball connoisseurs to better organize themselves in expression when enjoying this sport.